Integrative Taxonomy of Costa Rican Tetrigidae (Orthoptera) Reveals Eight New Species - Niko Kasalo; Daniel H. Janzen; Winnie Hallwachs; Allison Brown; Martin Husemann; Mathias Vielsäcker; Tomislav Domazet-Lošo; Damjan Franjević; Madan Subedi; Domagoj Bogić; Josip Skejo (Diversity)
Tetrigidae is one of the largest orthopteran families, but very few studies so far have integrated molecular and morphological data. Unsurprisingly, few species have been DNA barcoded, and the unresolved taxonomy makes Tetrigidae a difficult group to work with. Here, we examined a sample of 90 specimens collected as a part of the Costa Rican DNA barcoding project and identified 20 species assigned to 24 BINs, among which are 8 newly described species: Scaria bimaculata sp. nov., Lophotettix semicristatus sp. nov., Otumba auricarinata sp. nov., Otumba tenuis sp. nov., Otumba ignicula sp. nov., Metrodora mollilobata sp. nov., Metrodora ala sp. nov., and Platythorus inabsolutus sp. nov. We found that coloration and lateral lobe shape are species-specific among the examined species of Batrachideinae and Metrodorinae and that Lophotettiginae and Metrodora might be more closely related than previously assumed.